Cyanotoxins in Bloom Ever-Increasing Occurrence and Global Distribution of Freshwater Cyanotoxins from Planktic and Benthic Cyanobacteria - Kaloudis, Triantafyllos; Hiskia, Anastasia; Triantis, Theodoros (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
At present, cyanobacteria and their toxins (also known as cyanotoxins) constitute a major threat for freshwater resources worldwide. Cyanotoxin occurrence in water bodies around the globe is constantly increasing, whereas emerging, less studied or completely new variants and congeners of various chemical classes of cyanotoxins, as well as their degradation/transformation products are often detected. In addition to planctic cyanobacteria, benthic cyanobacteria, in many cases, appear to be important toxin producers, although far less studied and more difficult to manage and control. This Special Issue highlights novel research results on the structural diversity of cyanotoxins from planktic and benthic cyanobacteria, as well as on their expanding global geographical spread in freshwaters.